Fragipan Horizon Fragmentation in Slaking Experiments with Amendment Materials and Ryegrass Root Tissue Extracts - A. D. Karathanasis; L. W. Murdock; C. J. Matocha; J. Grove; Y. L. Thompson (The Scientific World Journal)
Slaking experiments were conducted of fragipan clods immersed in solutions of poultry manure, aerobically digested biosolid waste (ADB), fluidized bed combustion byproduct (FBC), D-H2O, CaCO3, NaF, Na-hexa-metaphosphate, and ryegrass root biomass. The fragipan clods were sampled from the Btx horizon of an Oxyaquic Fragiudalf in Kentucky. Wet sieving aggregate analysis showed significantly better fragmentation in the NaF, Na-hexa-metaphosphate, and ryegrass root solutions with a mean weight diameter range of 15.5–18.8 mm compared to the 44.2–47.9 mm of the poultry manure, ADB, and FBC treatments. Dissolved Si, Al, Fe, and Mn levels released in solution were ambiguous. The poor efficiency of the poultry manure, ADB, and FBC treatments was attributed to their high ionic strength, while the high efficiency of the NaF, Na-hexa-metaphosphate, and rye grass root solutions to their high sodium soluble ratio (SSR). A slaking mechanism is proposed suggesting that aqueous solutions with high SSR penetrate faster into the fragipan capillaries and generate the critical swelling pressure and shearing stress required to rupture the fragipan into several fragments. Additional fragmentation occurs in a followup stage during which potential Si, Al, Fe, and Mn binding agents may be released into solution. Field experiments testing these findings are in progress.